2017
DOI: 10.18820/24150525/comm.v22.3
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Marketing: Building Blocks for Mobile Content Marketing to Add Value and Relevance for Mobile Users

Abstract: INTRODUCTIONI think the biggest change, and the one we're already starting to see take shape, is that globally the majority of internet usage will be done via a mobile device and for most people the mobile web will be their primary -if not their only -way of experiencing the internet (Rojas, in Adler 2014).This prediction by Peter Rojas, formerly associated with the technology blog Gizmodo and currently with Engadget, became a reality when Google announced in 2015 that more than half of all searches are now d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…When a commodity price is lower than the reference point, a perceived benefit is generated and a consumer's desire to purchase is enhanced (Richmond, 1996). In order to attract consumers, businesses often adopt various promotion strategies, such as price discounts, prizes and raffles or coupons (Huang and Zhou, 2018;Du Plessis, 2017), which increase the economic benefits induced by mobile shopping platforms and stimulate consumers to generate exciting, positive emotional responses, and then generate impulsive buying. Hwang and Lee (2017) uncovered that leisure buyers were primarily interested on economic benefits when browsing a mobile shopping platform.…”
Section: Mobile Shopping Platform Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a commodity price is lower than the reference point, a perceived benefit is generated and a consumer's desire to purchase is enhanced (Richmond, 1996). In order to attract consumers, businesses often adopt various promotion strategies, such as price discounts, prizes and raffles or coupons (Huang and Zhou, 2018;Du Plessis, 2017), which increase the economic benefits induced by mobile shopping platforms and stimulate consumers to generate exciting, positive emotional responses, and then generate impulsive buying. Hwang and Lee (2017) uncovered that leisure buyers were primarily interested on economic benefits when browsing a mobile shopping platform.…”
Section: Mobile Shopping Platform Characteristicsmentioning
confidence: 99%
“…Almost all shopping platforms use similar promotion techniques, thus their influence on consumer's pleasure is limited. Therefore, a mobile shopping platform should give full play to its advantages of being free from time and space restrictions and fragmentation of consumer shopping time (Wang et al, 2015), adopting various promotion methods to attract consumer attention, such as price discounts, coupons, raffles or prizes (Huang and Zhou, 2018;Du Plessis, 2017), just to mention a few. The greater the savings brought by promotions, the more excited consumers become, and more likely they are to generate impulsive purchases (Rook, 1987).…”
Section: Mobile Shopping Platform Characteristicsmentioning
confidence: 99%
“…However, only some of the authors mentioned the importance of customers' inspiration and enablement, so it can be noted that content marketing does not try to motivate customers. The study also revealed that it is important to get involved (Ahmad et al, 2016;Dolezal, 2019), (co)create (Du Plessis, 2017b;2017c;Ho et al, 2020;Müller and Christandl, 2019), interact (Halevi and O'Hanlon, 2016;Dolezal, 2019), distribute information (Järvinen and Taiminen, 2016;Müller and Christandl, 2019;Repovienė, 2017), build relationships (Halevi and O'Hanlon, 2016;Pažėraitė and Gedvilaitė, 2018), share (Repovienė, 2017;Pažėraitė and Gedvilaitė, 2018;Ho et al, 2020), and manage (Ho et al, 2020;Pažėraitė and Gedvilaitė, 2016). The findings suggest that content marketing is essential, and the most important are (co)creation and distribution of information.…”
Section: Aims Of Content Marketingmentioning
confidence: 93%
“…Other authors perceive content marketing as a marketing method (Wall and Spinuzzi, 2018), the art of communication (Poradova, 2020), or a marketing technique (Halevi and O'Hanlon, 2016). Some authors do not attribute content marketing to any approach and perceive it as a practical activity (Du Plessis, 2017b;2017c;Liang et al, 2019;Holliman and Rowley, 2014;Järvinen and Taiminen, 2016). To sum up, there are two major approaches to content marketing; one perceives it as a strategy, and the other assigns it to undifferentiated practice.…”
Section: Area Of Content Marketingmentioning
confidence: 99%
See 1 more Smart Citation